Effect of Inoculation with Arbuscular Mycorrhizal Fungi on Green Gram Grown in Soil Containing Heavy Metal Zinc - swamy B. 1*, and Krishnappa. M2, Shivakumar C.K. 1, Hemavani C. 1, Thippe (Journal of Experimental Sciences, 2011)
Pot culture experiments were conducted to determine the effects of Arbuscular Mycorrhizal Fungi (AMF) on growth and Zn metal uptake by the green gram grown in soil containing 25, 50 and 100 mg kg-1 ZnSO4. AMF inoculated and non-AMF inoculated green grams were grown in sterilized substrates containing ZnSO4 and compared its effects on plant growth. Decreased Percentage of AMF colonization was observed with increasing in Zn concentration. Significant increase in root length, shoot length, total biomass, with decreased Zn uptake in shoot region was observed in AMF inoculated plants compared to AMF non-inoculated plants. High Zn accumulation was observed in the root region of mycorrhizal inoculated plant. Over all results indicate that AMF could promote the green gram growth with decreased Zn metal uptake from soil and thus protects the plant from metal toxicity.